Evaluation the Effect of Velocity and Temperature on the Corrosion Rate of Crude Oil Pipeline in the Presence of CO2/H2S Dissolved Gases - Hadi Jasim, Haider (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
In this paper investigate the influences of dissolved CO2/H2S gases, crude oil velocity and temperature on the rate of corrosion of crude oil transmission pipelines of Maysan oil fields southern Iraq. The Potentiostatic corrosion test technique was conducted into two types of carbon steel pipeline (materials API 5L X60 and API 5L X80). The computer software ECE electronic corrosion engineer was used to predict the influences of CO2 partial pressure, the composition of crude oil, flow velocity of crude oil and percentage of material elements of carbon steel on the rate of corrosion. As a result, the carbon steel API 5L X80 indicates good and appropriate resistance to corrosion compared to carbon steel API 5L X60. The rate of corrosion acquired from the test in flow conditions is most significant than that in static conditions. The crude oil from Noor field has the largest value of corrosion rate, while the crude oil from Halfaya field has the lower value; other crude oils have moderate values. The dissolved CO2/H2S gases contribute by a low degree in internal pipeline corrosion because of the small concentrations.